PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) BERBASIS LIVEWORKSHEET PADA MATERI SISTEM EKSKRESI - Nurmiati Nurmiati (Jurnal Inovasi Pendidikan dan Sains, 2022)
This research aims to develop and describe student worksheet on the excretory system materials. This research is an R&D (Research and Development) study based on the ADDIE development model, which consist of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. The research instruments used were validation sheet question and response quesionnaires. The students worksheet was validated by 3 experts: a subject matter expert, a media expert, and a biology lecturer and it was tested on students.The result showed the students worksheet the percentage of achievements was 90% according material expert, 94% according media expert, and 96% according biolgy lecturer. Meanwhile, the student testis resulted in a score of 83,9% with a very feasible criteria. The conclusion of this research is that student worksheet based liveworksheet on the excretory system are highly suitable for supporting the learning process